How to improve repetition ability in patients with Wernicke's aphasia: the effect of a disguised task. Issue 5 (15th April 2005) - Otsuki, M; Soma, Y; Yoshimura, N; Miyashita, K; Nagatsuka, K; Naritomi, H
Abstract : Dissociation "automatico-voluntaire" is a symptom observed in aphasic patients. We elucidated the difference between voluntary and involuntary speech output in a quantitative manner using the same task materials in nine patients with Wernicke's aphasia. All the patients exhibited better ability and less paraphasias in a repetition task elicited in a disguised condition than in an ordinary repetition condition. This result indicates that the output difficulty in Wernicke's aphasia might be a disability of volitional control over the language system.